ESSENTIAL OIL COMPONENTS IN SELECTED SPECIES OF ALPINIEAE (ZINGIBERACEAE) FROM SARAWAK AND ITS TAXONOMIC CORRELATION - Salasiah, Mohamad; Alona, C.L.; Meekiong, Kalu (Forest Research Institute Malaysia, 2022)
Alpinieae is recognised as the most complex tribe in the Zingiberaceae family, in terms of defining the morphological characters that delimit the genera. In the present study, essential oils from the rhizomes of selected Alpinieae species from Sarawak such as Alpinia galanga, A. ligulata, Conamomum cylindrostachys, C. xanthophlebium, Etlingera coccinea, E. nasuta, Hornstedtia leonurus, Plagiostachys strobilifera var. strobilifera, P. strobilifera var. conica, Sundamomum corrugatum and S. laxesquamosum were analysed using GC-MS and hierarchical clustering. Phytochemical analysis revealed the major and specific components that grouped and characterised the studied taxa in their respective cluster. Close relationship between the studied Conamomum, Sundamomum and A. ligulata with P. strobilifera var. conica were also shown at 70%, 94% and 60% similarity index, respectively. The clustering based on chemometric data corresponded to the morphology of the inflorescence, anther crest, lateral staminodes and fruit. The present findings had provided supplementary evidence to a better understanding especially on the ambiguity status of some problematic genera in the tribe including Alpinia, Plagiostachys and Hornstedtia.